2019
DOI: 10.3390/nu11051130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lactitol and Psyllium on Bowel Function in Constipated Indian Volunteers: A Randomized, Controlled Trial

Abstract: Psyllium and lactitol have been reported to increase fecal volume, moisture content and bowel movement frequency (BMF). However, the benefits of their combined use on constipation has not been examined. The aim of this study was to evaluate the effects of a 4-week intervention with lactitol and/or psyllium on bowel function in constipated volunteers. Adults (N = 172) who were diagnosed with functional constipation per Rome III criteria were randomized to four treatment groups: 10 g lactitol, 3.5 g psyllium, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It has been proven that polysaccharides derived from these plants reduce cholesterol and blood glucose, have anti-inflammatory and antioxidant activities, and are anticarcinogenic. They are also a good source of dietary fiber [135,136]. Based on the antiallergic and antimicrobial properties of mucilage from P. ovata, a mouthwash containing polysaccharides and vinegar was developed.…”
Section: Plantagomentioning
confidence: 99%
“…It has been proven that polysaccharides derived from these plants reduce cholesterol and blood glucose, have anti-inflammatory and antioxidant activities, and are anticarcinogenic. They are also a good source of dietary fiber [135,136]. Based on the antiallergic and antimicrobial properties of mucilage from P. ovata, a mouthwash containing polysaccharides and vinegar was developed.…”
Section: Plantagomentioning
confidence: 99%
“…It is in powder form that should be mixed with a beverage once a day. It has been demonstrated to increase fecal volume, moisture content, and bowel movement frequency (Cheng et al 2019 ). Its most common AE are upper respiratory infections, gassiness, diarrhea, and increased creatinine phosphokinase levels.…”
Section: Gastroenterologymentioning
confidence: 99%
“…Psyllium was also associated with improved stool consistency at various time points. In the third placebo-controlled trial, which also included lactitol and psyllium + lactitol as comparators, there were no significant differences between any of the 4 groups in terms of stool frequency (primary endpoint), stool consistency, QoL, or patient-assessed symptoms in subjects with self-reported constipation (<3 BMs/week) ( 54 ). In other comparative trials, lactulose ( 55 ), mango ( 45 ), and prunes ( 44 ) significantly outperformed psyllium in stool frequency and consistency.…”
Section: Resultsmentioning
confidence: 99%
“…The data are most robust for psyllium. However, it is worth noting that the highest graded placebo-controlled psyllium study ( 54 ) revealed no significant benefit over placebo and head-to-head trials revealed that psyllium is less effective than comparator agents (e.g., PEG, lactulose, and fruits). Psyllium: Level II Evidence, Grade B Recommendation Polydextrose: Level I Evidence, Grade I (Insufficient) Recommendation Inulin: Level I Evidence, Grade I (Insufficient) Recommendation Mixed Fiber: Level II Evidence, Grade B Recommendation …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation